The Warren Buffett way investment strategies of the world's greatest investor - Hagstrom, Robert G. 1956- (Wiley, 1994)
Describes the career, and investment techniques and philosophy of Warren Buffett who began with an investment of
Keywords: Buffett, Warren; Buffett, Warren -- 1930-; Agents de change - États-Unis - Biographies; Capitalistes et financiers - États-Unis - Biographies; Investeringen; Investissements - États-Unis; Spéculation - États-Unis; Capitalists and financiers -- United States -- Biography; Investments -- United States; USA; Biografie